A Framework for Applying the Learning Sciences to MOOC Design - Gordon, Darcy G.; Wiltrout, Mary Ellen (Frontiers in Education, 2021)
Evidence-based practices grounded in the learning sciences provide an opportunity for improved learning experiences in traditional in-person, as well as in hybrid and online environments. We advocate specifically that large-scale, online learning experiences, such as Massive Open Online Courses (MOOCs) can benefit from applications of the learning sciences. To that end, we present a description of how and why we use specific learning science practices in a biochemistry MOOC with the intention to contribute to the discussion about the quality of online learning experiences, and lower the barrier for other practitioners seeking a framework for implementing evidence-based course design. We believe that the application of the learning sciences can make online learning experiences more rigorous and effective, and practitioners should optimize the use of these strategies through clever tests in specific contexts.